Screening Study for Finding the Optimal Combination Gel Composition for the Treatment of Periodontal Disease, Which Contains Extracts of Aloe Vera and Oak Bark - Tsubanova, Natalia (Asian Journal of Pharmaceutics (AJP), 2017)
Introduction: Today in many countries, there is a clear trend to a growing number of major diseases of the oral cavity, due to the poor state of the environment, unbalanced diet, and concomitant chronic diseases of the gastrointestinal tract. Topical problem of modern medicine and pharmacy is optimization of pharmacotherapy of inflammatory periodontal diseases. The aim of the study was to establish optimal combination of new gel for the treatment of periodontal disease. Materials and Methods: The experimental studies were conducted on white male rats. Research of membrane protective activity was carried out on the standard model of spontaneous hemolysis of erythrocytes by Jager. The research of antimicrobial activity was carried out by method of diffusion in agar. Research of Parodont-protective effect was carried out on the model protamine periodontitis. Results and Discussions: Extract of Aloe has powerful membrane protective effect in different doses. The study in vitro showed the high sensitivity of thick oak bark extract in the form of a gel to the cultures of Staphylococcus aureus, Pseudomonas aeruginosa, Bacillus subtilis, and Candida Ð°lbicans that allows to recommend it for the treatment of inflammatory diseases of the mouth. Conclusions: According to the results of screening studies, optimal composition of gel that contains Ðloe arborescens and cortex Quercus were selected for the treatment of parodontal diseases. Parodont-protective activity of gel is confirmed on the protamine periodontitis model, the ability to decrease the clinical symptoms, namely, hyperemia, edema and necrotic erosive changes of the gums and mucous membranes of the mouth.